(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2014)
The behavior of composite beams with circular web openings is described. Four composite beams comprising one control beam were tested. The perforated beams have six circular openings with various locations. Opening size was fixed (66.7% of the steel section web depth) while number of openings in each composite beam was varied. Deflections at midspan and at openings were observed. Cracking of concrete slab and behavior of each opening were explained in detail. Tests indicated that circular web opening reduced the strength of composite beams. The behavior of composite beams relatively unaffected by the presence of circular web openings up to first yield. Less effect for the inclusion of circular web openings located out of midspan. The concrete slab has limited contribution to the strength of composite beams with circular web openings.